﻿Capturing the Benefits of Genetically Modified Organisms for the Poor - Ragasa, Catherine; Pehu, Eija (World Bank, 2012)
The controversy swirling around GMOs in rich countries should not obscure their potential to reduce poverty among poor farmers.